2017
DOI: 10.1103/physrevfluids.2.024303
|View full text |Cite
|
Sign up to set email alerts
|

Diffusivity and hydrodynamic drag of nanoparticles at a vapor-liquid interface

Abstract: Measurements of the surface diffusivity of colloidal spheres translating along a vapor/liquid interface show an unexpected decrease in diffusivity, or increase in surface drag (from the Stokes-Einstein relation) when the particles situate further into the vapor phase. However, direct measurements of the surface drag from the colloid velocity due to an external force find the expected decrease with deeper immersion into the vapor. The paradoxical drag increase observed in diffusion experiments has been attribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 53 publications
2
21
0
Order By: Relevance
“…For typical values for the translational velocity U of order of 10 −3  ms −1 (values measured for capillary attraction 812 ), colloid densities of order 10 3 –10 4  kg m −3 , liquid density and viscosity of order 10 3  kg m −3 and 10 −3  kg m −1 s −1 , respectively, and surface tension of the order of 10 mNm −1 , colloid diameters should be less than approximately 10  μ m for Bo  < 10 −2 and Re  < 10 −2 which infers that the colloid size range which satisfies the restrictions of our study approach the colloid domain. For nanoparticles, the diffusion and forced motion of nanoparticles on fluid interfaces have been studied theoretically using molecular dynamics simulations 13,14 without gravity and low to order one Reynolds number, and noticeable meniscus curvature at the contact line was not observed, either as the colloids diffused along the surface or were forced to move by an external force.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For typical values for the translational velocity U of order of 10 −3  ms −1 (values measured for capillary attraction 812 ), colloid densities of order 10 3 –10 4  kg m −3 , liquid density and viscosity of order 10 3  kg m −3 and 10 −3  kg m −1 s −1 , respectively, and surface tension of the order of 10 mNm −1 , colloid diameters should be less than approximately 10  μ m for Bo  < 10 −2 and Re  < 10 −2 which infers that the colloid size range which satisfies the restrictions of our study approach the colloid domain. For nanoparticles, the diffusion and forced motion of nanoparticles on fluid interfaces have been studied theoretically using molecular dynamics simulations 13,14 without gravity and low to order one Reynolds number, and noticeable meniscus curvature at the contact line was not observed, either as the colloids diffused along the surface or were forced to move by an external force.…”
Section: Introductionmentioning
confidence: 99%
“…However recently, evaluating the drag exerted on non-smooth colloids 14 with heterogeneous surfaces as they diffuse along an interface while specifically examining the role of contact line pinning and de-pinning have been important given the extensive interest in particle-laden interfaces. For the translational motion with velocity U , the fluid exerts a drag in the opposite direction to the motion calculated in terms of a drag coefficient (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…These discrepancies indicate that our simple model is not able to completely catch the complex physics ruling the dynamics of active particles at air–liquid interfaces. The hydrodynamics of active and passive particles trapped at the interface between two immiscible fluids is a topic that has been attracting the interest of a wide community (Boniello et al., ; Dani, Keiser, Yeganeh, & Maldarelli, ; Koplik & Maldarelli, ; Malgaretti, Popescu, & Dietrich, ) and a detailed discussion is out of the aim of this study. Keeping our argumentation in the framework of the presented toy model, our results indicated that we are slightly underestimating the torque or overestimating the drag (or both of them).…”
Section: Discussionmentioning
confidence: 99%
“…The simulations are conducted in a canonical/NVT ensemble, where the temperature is fixed at 0.8E/k B using a Nosé-Hoover thermostat. This particular solid/liquid system has been used in a number of previous simulations (Busic, Koplik & Banavar 2003;Koplik et al 2006;Koplik & Maldarelli 2017), and its properties are well characterized. The liquid has bulk number density 0.857σ −3 , viscosity 5.18m/(σ τ ) and liquid-vapour surface tension 0.668E/σ 2 , where m is the mass of the liquid atoms and τ = σ (m/E) 1/2 is the natural time scale based on the LJ parameters.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%